Description of the Larva of Athous monilicornis (Coleoptera, Elateridae), with Notes on the Species Distribution - Penev, L. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
First description of the larva of Athous (Haplathous) monilicornis Schwarz, 1897, a species endemic to the Balkan Peninsula, known so far from Bulgaria, and reported in this paper from Macedonia and Greece as well. The larva differs from the other representative of subgenus Haplathous occurring in the high mountains of Bulgaria Athous subfuscus (Muller), by the width of the pit of the urogomphi. Athous monilicornis is confined to the subalpine habitats and the upper coniferous forests belt of the mountains of Bulgaria, Macedonia and Greece. Впервые описана личинка щелкуна Athous (Haplathous) monilicornis Schwarz, 1897, вида, эндемичного для Балканского п-ова и известного из Болгарии, а также Греции и Македонии. От личинок встречающегося в высокогорьях Болгарии Athous (Haplathous) subfuscus (Muller) отличается шириной ямки на урогомфах. Распространение A. monilicornis в горах Болгарии, Македонии и Греции ограничено субальпикой и верхней частью пояса хвойного леса.